Impact of moisture content and maize weevils on maize quality during hermetic and non-hermetic storage. (September 2018) - Suleiman, R.; Bern, C.J.; Brumm, T.J.; Rosentrater, K.A.
Abstract: The objective of this study was to determine the impact of moisture content and Sitophilus zeamais Motschulsky on maize quality during hermetic and non-hermetic storage conditions. Commercial Channel 211-97 hybrid maize kernels were conditioned to 14, 16, 18, and 20% moisture content (wet basis), and then three replications of 300 g of maize grain were stored in glass jars or triple Ziploc ® slider 66-μm(2.6-mil) polyethylene bags at four conditions: hermetic with weevils, hermetic no-weevils, non-hermetic with weevils, non-hermetic no-weevils. All jars and bags were stored in an environmental chamber at 27 °C and 70% relative humidity for either 30 or 60 d. At the end of each storage period, jars and bags were assessed for visual mold growth, mycotoxin levels, gas concentrations, pH level, the numbers of live and dead S. zeamais, and maize moisture content. The maize stored in non-hermetic conditions with weevils at 18 and 20% exhibited high levels of mold growth and aflatoxin contamination (>150 ppb). Conversely, very little mold growth was observed in maize stored in hermetic, and no aflatoxins were detected in any moisture level. CO2 increased and O2 gradually decreased as storage time increased for maize stored in hermetic conditions (with or without weevils) in all moisture level. No significant difference in pH was observed in any storage conditions ( P  < 0.05). Total mortality (100%) of S. zeamais was observed in all hermetically stored samples at the end of 60 days storage. Moisture content for hermetically stored maize was relatively constant. A positive correlation between moisture content and storage time was observed for maize stored in non-hermetic with weevils (r = 0.96, P  < 0.05). The results indicate that moisture content and the number of S. zeamais weevils plays a significant role in maize storage, both under hermetic and non-hermetic conditions. Highlights: Little or no mold growth was visible for maize stored under hermetic conditions. Maize stored in non-hermetic conditions with weevils at 18 and 20% exhibited very high levels of mold growth and aflatoxin contamination. No aflatoxins were detected in any maize stored in hermetic conditions or at low moisture content (14%). CO2 increased and O2 gradually decreased as storage time increased under hermetic conditions. No significant difference in pH was observed amongst any storage conditions.